Alternatif Fortification Vitamin A for Lactating Mother Using Siomay Sauce Enriched with Red Palm Oil - Budiyanto Budiyanto; Devi Silsia; A. Napitupulu (AGRITROPICA : Journal of Agricultural Sciences, 2019)
Siomay is a popular street foods in urban and rural areas of Indonesia. Due to its characteristics siomay sauce can be incorporated with RPO (RPO)  for vitamin A fortification.  The objective of the study were determining the effect of RPO addition to the characteristic of siomay sauce, and  determining the preference of siomay sauce added with various amount of RPO.  A four levels addition of RPO (0.0 g, 1.5 g, 3.0 g and 4.5 g) were added to siumay sauce. The physical characteristics  (viscosity, emulsion stability), sensory evaluation (hedonic test and duo-trio test) of the sauce, and the retinol equivalent of fortified siomay sauce were evaluated.   The result showed that  viscosity of siomay sauce increased with increasing addition of RPO into the sauce.   The hedonic test revealed that  the overall preference of original siomay sauce added with 4.5 g of RPO was not significantly diferent from the controll.   In addition, siomay sauce enriched with 4,5 g RPO could increase  325.22 ?g   retinol equivalents (RE) or equal to 38.26 % of the RDA of vitamin A for lactating woman.  The finding suggest that siomay sauce fortified with RPO could be used for combating Vitamin A deviciency.